2023
DOI: 10.1186/s40834-022-00208-6
|View full text |Cite
|
Sign up to set email alerts
|

Perceived motivators, knowledge, attitude, self-reported and intentional practice of female condom use among female students in higher training institutions in Dodoma, Tanzania

Abstract: Background Unplanned pregnancies and sexually transmitted infections (STIs) Human Immunodeficiency Virus (HIV) inclusive, have remained to be a significant public health challenges among young people, especially across middle and low-income countries. Self-efficacy on the right ways of using condoms appears to be effective against the aforementioned health-related problems. However, most women of reproductive age tend not to use them when they are using highly effective contraceptives such as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The tools were confirmed to be clear and no further editing and deletion of the items were done, but it was translated into the Swahili language to blend to the literacy level of the study participants. As suggested by previous scholars (Millanzi, Herman, & Ambrose, 2023 ; Millanzi, Herman, & Mtangi, 2023 ; Mwanja et al., 2023 ; Shitindi et al., 2023 ), the data collection tool was pre‐tested among 30 adults aged 18 years and above at a different location from where the actual data collection was conducted to assure its validity and reliability. Respondents filled all items in the questionnaires entirely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tools were confirmed to be clear and no further editing and deletion of the items were done, but it was translated into the Swahili language to blend to the literacy level of the study participants. As suggested by previous scholars (Millanzi, Herman, & Ambrose, 2023 ; Millanzi, Herman, & Mtangi, 2023 ; Mwanja et al., 2023 ; Shitindi et al., 2023 ), the data collection tool was pre‐tested among 30 adults aged 18 years and above at a different location from where the actual data collection was conducted to assure its validity and reliability. Respondents filled all items in the questionnaires entirely.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 1, the study involved 312 out of 12,584 randomly sampled adults in the Dodoma region. As it has also been used by some previous studies (Millanzi, 2022;Millanzi et al, 2020Millanzi et al, , 2021Millanzi, Herman, & Ambrose, 2023;Millanzi, Herman, & Mtangi, 2023;Millanzi, Osaki, et al, 2023;Mwanja et al, 2023;Shitindi et al, 2023), a proportionate formula was adopted based on the available number and level of health facilities that were stratified into dispensaries (n = 1: in one district) health centres (n = 2: in three districts), district hospitals (n = 2: in 6 districts) and referral hospital (n = 1: in Dodoma region). A simple random sampling technique by lottery methods was used to get study participants.…”
Section: Sampling Procedures and Sample Sizementioning
confidence: 99%
“…Chi-square and cross-tabulation were used to determine the relationship between variables. As it has been used by previous studies [ 30 , 31 ] shown in the statistical formula number two (2), a binary and multinomial logistic regression model was performed to determine the association between the predictor variables and the outcome of interest under study at a 95% confidence interval and a 5% significance level.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the recommendations from previous scholars [25][26][27], The following procedures were performed to determine the minimum sample size for the study using the formula by Cochran 1977 [28].…”
Section: Study Population and Sample Size Determinationmentioning
confidence: 99%